PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN DAYA TAHAN AEROBIK PEMAIN SEPAKBOLA UNIVERSITAS BINA DARMA - Satria, M. Haris (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
This study aimed to determine the Effect of Circuit Training Exercises to increase the Aerobic Endurance of Bina Darma University Football Players. This type of research is experimental research. The study sample amounted to 17 people. The instrument used was the BLEP test. The data analysis technique used SPSS statistics 23. The result of this study indicated that circuit training exercise can increase the aerobic endurance of Bina Darma University soccer players. The t test showed that t_ (count) = 6,564> t_ (table) = 1,740 so that the accepted Ha is significant. Suggestion from this research is that trainers can use the circuit training method to increase the aerobic endurance of athletes.